MEMAHAMI RITUAL KEMATIAN DALAM TRADISI MASYARAKAT TANIMBAR - Batlayeri, Willem; Rahawarin, Bernard Antonius (Fides et Ratio : Jurnal Teologi Kontekstual Seminari Tinggi St. Fransiskus Xaverius Ambon, 2018)
This writing is the result of reasearch and analysis of a death ritual according to Tanimbarese tradition. The purposes of this research investigate and find out about the concept, ritualization and effect of the death ritual which is performed on deceased people in the Tanimbar Islands. In relation to the challenge of this study, we use some theories, derived from the Catholic Church and from a post-structuralist like Michael Foucault, to analyse this traditional Tanimbarese death ritual.